Sodstvo in Ustavno sodišče RS - Knez, Rajko (Podjetje in delo, 2020)
The article focuses on two procedures before the Constitutional Court, in which a judicial dialogue between the so-called regular courts and the Constitutional Court exists. The first one, a request for review of the constitutionality, is based on the loyal cooperation among the courts and entails an abstract review. The subjectivity (parties) of the dispute is not in foreground. The second one, the constitutional complaint procedure, entails a review of reasons used by the regular courts from the constitutional level. The article does not pore over the rules that regulate both procedures, but rather focuses on some subtopics. Firstly, it discusses the so-called need for judicial protection in procedures for the abstract review. With regard to the constitutional complaint procedure, two subtopics are emphasised: the subtleness of the substantive exhaustion of legal remedies and the quality of the reproaches, which can lead, in connection with the absence of the reasons on which the judgements are based, to different substantive decisions by the ECtHR. A topic regarding the increasingly frequent judicial dialogue with the first and second level regular courts is also added.
Keywords: 160. člen Ustave RS; a constitutional complaint; a request for review of the constitutionality; Art. 156 of the Constitution; Constitutional Court; državno odvetništvo; European Court of Human Rights; Evropsko sodišče za človekove pravice; exhaustion of legal remedies; izčrpanje pravnih sredstev; judicial dialogue; redna sodišča; regular courts; Schumann`s formula; Schumannova formula; sodniški dialog; state attorney; ustavne pritožbe; Ustavno sodišče; zahteve za oceno ustavnosti